2018
DOI: 10.1177/1469066718798097
|View full text |Cite
|
Sign up to set email alerts
|

Relative glycosidic bond stabilities of naturally occurring methylguanosines: 7-methylation is intrinsically activating

Abstract: The frequency and diversity of posttranscriptional modifications add an additional layer of chemical complexity beyond canonical nucleic acid sequence. Methylations are particularly frequently occurring and often highly conserved throughout the kingdoms of life. However, the intricate functions of these modified nucleic acid constituents are often not fully understood. Systematic foundational research that reduces systems to their minimum constituents may aid in unraveling the complexities of nucleic acid bioc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 98 publications
(160 reference statements)
0
6
0
Order By: Relevance
“…Unstable glycosidic bonds accelerate depurination and formation of abasic sites on nucleic acids, which may ultimately contribute to cell cytotoxicity [67]. Destabilization of the glycosidic bond can be caused by a change in chemical composition of the nucleoside due to certain modifications such as methylation [45, 47, 68]. Previous evaluation of the effects of cisPt modification on guanosine residues indicated that platination has no significant effect on glycosidic bond stability [52].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Unstable glycosidic bonds accelerate depurination and formation of abasic sites on nucleic acids, which may ultimately contribute to cell cytotoxicity [67]. Destabilization of the glycosidic bond can be caused by a change in chemical composition of the nucleoside due to certain modifications such as methylation [45, 47, 68]. Previous evaluation of the effects of cisPt modification on guanosine residues indicated that platination has no significant effect on glycosidic bond stability [52].…”
Section: Resultsmentioning
confidence: 99%
“…The ligands of AlaPt or OrnPt likely cause electron-density withdrawal at the N9 position in a manner that is dependent on proximity of the platinum atom. Further tandem mass spectrometry and spectroscopic studies, including computational analysis, are ongoing in an effort to elucidate detailed mechanisms for glycosidic bond cleavage of the N7 and N1/N3 AlaPt and OrnPt adduct species, as done previously with both standard and modified nucleosides [42, 46, 68].…”
Section: Resultsmentioning
confidence: 99%
“…Survival yield analysis is a robust method to determine the relative stabilities of precursor ions. , For the ER-CID experiments of protonated uridine and the 5-halouridine nucleoside analogues, the survival yield of the precursor ion was calculated at each rf excitation amplitude examined using eq , Survival yield = I p / ( I p + i I f i ) where I p and ( I p + ∑ i I f i ) are defined as in eq . The survival yields were calculated using custom software developed in our laboratory.…”
Section: Experimental and Computational Sectionmentioning
confidence: 99%
“…CID MS/MS spectra for [Adofl+H] + and [Guofl+H] + acquired at an rf EA near their CID 50% value are shown in Figure 2. Previously published [39,40] [39,40,53,54,67,68], as well as for the protonated noncanonical purine 2′-O-methylnucleosides, [Adom+H] + and [Guom+H] + [44], and other protonated and sodium cationized noncanonical methylguanosines [45]. The pyrimidine [Nuofl+H] + , [Nuo+H] + , and [dNuo+H] + also primarily undergo N-glycosidic bond cleavage [41][42][43][69][70][71]; however, several competing neutral loss pathways are also observed for the protonated uracil and thymine nucleoside analogues.…”
Section: Cid and Irmpd Dissociation Pathwaysmentioning
confidence: 99%
“…The solvent-free and controllable chemical environment of tandem mass spectrometry (MS/MS) experiments has proven an invaluable asset in the study of various aspects of the canonical and noncanonical DNA and RNA constituents. For example, energy-resolved collisioninduced dissociation (ER-CID) experiments performed under multiple collision conditions in trapping mass spectrometers have been used to study the relative stability of various nucleosides [9,[39][40][41][42][43][44][45]. Additionally, threshold analysis of ER-CID experiments performed under nominally single collision conditions on guided ion beam mass spectrometers (GIBMS) have provided thermodynamically accurate dissociation energetics for various noncovalent [46][47][48][49][50][51][52] and covalent [53][54][55][56] interactions of nucleobases and nucleosides.…”
mentioning
confidence: 99%